2008
DOI: 10.1186/1477-7800-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Patient choice significantly affects mastectomy rates in the treatment of breast cancer

Abstract: Mastectomy rates may be affected by patient choice. 203 patients who had a Total Mastectomy for breast cancer were invited to complete questionnaires at routine follow up clinics to ascertain if they had been offered a choice of Breast Conserving Surgery (BCS), and to establish the reasons for their preference. Questionnaires were checked against medical and nursing records to confirm the reasons for the patients' choice of mastectomy. 130 patients (64%) chose to have a mastectomy, reporting that they felt saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 7 publications
1
22
0
Order By: Relevance
“…If despite this information the patient is resolute in their decision then follow up contact pre-operatively to ensure that they remain so may be prudent. Previous studies have identified that patients feel safer after mastectomy, and that fear of recurrence and perceived survival benefit are primary motivators for choosing a mastectomy over BCS (23,24), and fear or recurrence remains an issue in the longterm, which is a challenge (25,26). Given these beliefs it may be that the communication of adverse pre-operative pathological features may influence the patient's decision to pursue mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…If despite this information the patient is resolute in their decision then follow up contact pre-operatively to ensure that they remain so may be prudent. Previous studies have identified that patients feel safer after mastectomy, and that fear of recurrence and perceived survival benefit are primary motivators for choosing a mastectomy over BCS (23,24), and fear or recurrence remains an issue in the longterm, which is a challenge (25,26). Given these beliefs it may be that the communication of adverse pre-operative pathological features may influence the patient's decision to pursue mastectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Even though total mastectomy rates alone are not an accurate measurement for breast cancer care, they bring an insight into the complex issues involved in surgical management of the disease. 16,22,24,25,[28][29][30][31][32][33][34][35]47 In our study, one of these issues is the increasing frequency of early breast cancer at the time of surgery, which is a necessary condition for performing BCS, and is associated with better patient outcomes.…”
Section: Frommentioning
confidence: 99%
“…Athas and colleagues suggested that up to 30 per cent of patients who undergo BCS for early breast cancer do not receive postoperative breast irradiation because they live a substantial distance away from a RT centre, or have significant co‐morbidities or serious difficulties preventing them from attending daily treatment, especially the elderly. Because of this, in some countries patients decline RT or even opt for mastectomy to avoid radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The local recurrence rate (LRR) after BCS and conventional radiotherapy (RT) is estimated to be under 1 per cent per year, and varies between 4 and 7 per cent at 5 years 4,5 . The additional administration of an external radiation boost of [10][11][12][13][14][15][16] Gy to the tumour bed can further reduce the LRR by 40 per cent 6 . The landmark UK Standardization of Breast Radiotherapy (START) A and START-B studies found that the conventional schedule of 50 Gy in 25 fractions could be safely reduced to 41⋅6 Gy in 13 fractions and 40 Gy in 15 fractions respectively over 3 weeks 7 -10 .…”
Section: Introductionmentioning
confidence: 99%